2020
DOI: 10.3390/medicina56050235
|View full text |Cite
|
Sign up to set email alerts
|

Could FeNO Predict Asthma in Patients with House Dust Mites Allergic Rhinitis?

Abstract: Background and Objectives: The evolution of allergic rhinitis to asthma is a part of “atopic march”. The aim of this study was to analyze possible predictive markers for asthma occurrence in patients with allergic rhinitis to house dust mites (HDM). Materials and Methods: Fifty-eight patients with persistent allergic rhinitis (PAR) were included. The clinical, biological evaluation and fractionated exhaled nitric oxide (FeNO) measurement were performed at enrolment. The patients were clinically evaluated after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Maintaining good asthma control helps minimize the risk of asthma exacerbation as other studies have shown [ 23 , 28 ]. The group of uncontrolled asthma patients in our study representing 55.2%, was probably due to persistent inflammation in the lower airways even before symptoms appeared [ 29 ]. Preexisting airway inflammation may lead to exacerbation during a viral respiratory infection or in presence of other triggers, as other studies showed inflammatory diseases exacerbations during and after COVID-19 [ 1 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining good asthma control helps minimize the risk of asthma exacerbation as other studies have shown [ 23 , 28 ]. The group of uncontrolled asthma patients in our study representing 55.2%, was probably due to persistent inflammation in the lower airways even before symptoms appeared [ 29 ]. Preexisting airway inflammation may lead to exacerbation during a viral respiratory infection or in presence of other triggers, as other studies showed inflammatory diseases exacerbations during and after COVID-19 [ 1 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the evaluation included the test performance against atopic dermatitis and allergic rhinitis, both known to contribute to the increase in FeNO [ 29 ]. It seems that allergic rhinitis plays a key role in subclinical inflammation in the lower airways [ 30 ]. The focus on currently treated asthma and not for asthma ever was justified by better reliability of the former manifestation of disease even if diagnosed based on the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, patients with clinical manifestations induced by grass pollen were included, even if some of them were sensitized to several allergens. The inflammatory response in pollen allergy may differ toward house dust mite allergic patients, due to different aspects of the allergens (perennial, dimensions, enzymatic properties) [ 42 , 43 , 44 , 45 ], but this hypothesis needs further investigation. Another reason for the low reduction in total IgE could be related to polysensitization of the patients, even if they did not report clinical manifestation during the grass pollen season.…”
Section: Discussionmentioning
confidence: 99%